MANAGEMENT OF HEMODYNAMIC INSTABILITY IN CRITICALLY ILL PATIENTS UNDERGOING HEMODIALYSIS (REMUNOM, 2025)
Hemodialysis is commonly indicated in critically ill patients for various conditions, including acute kidney injury (AKI). During dialysis therapy, episodes of significant hemodynamic instability can occur, notably arterial hypotension. This integrative review aimed to identify and synthesize current strategies for managing hemodynamic instability induced by hemodialysis in critically ill patients. The search for articles between 2015 and 2025 was conducted in the PubMed/MEDLINE, CINAHL, Cochrane Library, LILACS, and BDENF databases. 105 studies were found. After applying inclusion and exclusion criteria, 5 articles were selected for full-text reading. The results showed that the most effective strategies for preventing and managing intradialytic hypotension are intravenous albumin infusion and the use of cold dialysate. Sodium modulation can also be effective when combined with an ascending-descending UF profile. More multicenter studies with larger samples are needed to better guide clinical practice.